When Not Only the Stadium Grass is Green - Makara, Emese; Ráthonyi-Ódor, Kinga (Acta Carolus Robertus, 2024)
The issue of sustainability is one of the most prominent challenges of our time, requiring active involvement from economic, social, political, and industrial segments. The sports sector is no exception, as almost every activity related to sports can be linked to environmental damage, such as stadium construction, operation, organization of sports events, fan and consumer behavior, etc. The relationship between sports and the environment is periodic, often negatively affecting the natural environment, land use, air pollution, water use, energy and resource needs, carbon dioxide emissions, waste management issues, posing cardinal problems for the urban atmosphere and living space. One area where the aforementioned points are exponentially prominent is the construction of large stadiums, which host various teams' sporting events. Although the economic benefits of events held in these facilities and the satisfaction and euphoria felt by fans and residents are undeniable, it is crucial for stakeholders to examine and address sustainability shortcomings.The aim of this study is to present the sustainability and environmental pollution reduction efforts of two domestic and one foreign football stadiums, focusing on the examination of the sports facilities of DVTK, Szeged-Csanád Grosics Academy and FK TSC.
Keywords: football stadiums; sustainability; environmental protection